Novel NUDCD1 gene variant predisposes to severe COVID-19 disease in Asians through modulation of antiviral DHX15- and MAVS-mediated signalling - Anusha Amali, Aseervatham; Tay, Douglas Jie Wen; Seow, Yiqi; Loh, Marie; Ravikumar, Sharada; Yu, Jocelyn Jin; Loong, Shaun Seh Ern; Fong, Siew Wai; Lee, Chang Jie Mick; Lim, Jonathan Jordon Cailu; Gan, Louis Hanqiang; Koh, Winston Lian Chye; et al. (Frontiers in Immunology, 2025)
BackgroundGenome-wide associative studies can potentially uncover novel pathways which modulate anti-viral immune responses against SARS-CoV-2 or identify drivers of severe disease. To date, these studies have yielded loci mostly in non-functional domains of unknown biological significance and invariably require large sample sizes, potentially missing lower frequency variants, especially in under-represented or minority populations.MethodsTo identify unique genetic traits predisposing to severe COVID-19 in Asians, we employed an alternative strategy using whole exome sequencing of representative cohort of severe versus mild COVID-19 patients. Candidate gene variants were identified by performing logistic regression against top genetic principal components, prioritised for missense variants with likely causal impact. Then, functional sequelae of variants were replicated in-vitro and re-validated in patients ex vivo to demonstrate causality between genotype and clinical phenotype.ResultsOf 136 COVID-19 patients in Singapore (of whom 25% had severe disease), a single nucleotide polymorphism rs2980619 (p.L252F substitution) belonging to NudC-Domain-Containing-1 (NUDCD1) was highly-placed. Homozygous bearers of variant p.L252F had higher (3.97x) odds of severe disease. Age >50 years and male sex were significant covariates which increased the odds of severe disease by 3.38x and 3.16x, respectively. We showed in-vitro that variant p.L252F reduced NUDCD1 activity, leading to reduced antiviral signalling through RNA helicase DHX15 and antiviral signalling adaptor MAVS, reduced activation of NFκB components RelB and p65, and resultant 1-log higher SARS-CoV-2 viral load compared to wild type (L252) cells. Patients bearing p.L252F had lower NUDCD1, MAVS, and RelB expressions, affirming the above findings.ConclusionA gene variant of NUDCD1 influences COVID-19 severity in Asians through interacting with DHX15 and MAVS, affecting effective response against SARS-CoV-2.